Implementasi Artificial Intelligence dalam Sistem Pembelajaran Adaptif Berbasis Web pada Pendidikan Tinggi - Rahman Peliza (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
The development of Artificial Intelligence (AI) technology has brought significant changes in the digital learning system, especially in higher education. One of the promising applications of AI is a web-based adaptive learning system that is able to adjust the material, methods, and level of learning difficulty according to the characteristics and needs of each student. This research aims to implement Artificial Intelligence in web-based adaptive learning systems and analyze its impact on the effectiveness of student learning. The research method used is a system development method with a user-centered design approach, which includes the stages of needs analysis, system design, implementation of AI algorithms, and system evaluation. The system was developed by utilizing machine learning algorithms to model student learning profiles based on user interaction data. The results of the study show that AI-based adaptive learning systems are able to increase user engagement, learning effectiveness, and student satisfaction with the online learning process. This research is expected to be a reference for the development of a more personalized and data-based digital learning system in the higher education environment.